Mpu Uteun: The Role and Challenges of Female Initiators in Preserving Forest Functions - Fatia, Dara; Alfina, Melisa (Department of Anthropology, 2025)
Forest degradation in Aceh, particularly in Damaran Baru Village, has triggered ecological disasters that directly affect the lives of local communities, especially women. Motivated by environmental concern and a sense of responsibility, a group of women led by a female initiator established Mpu Uteun, a community-based forest protection initiative. This study aims to examine the roles and challenges faced by female initiators in preserving forest functions through the activities of Mpu Uteun. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews, and documentation, with informants selected purposively. The findings reveal that Mpu Uteun plays a vital role in forest conservation through regular patrols, legal advocacy for social forestry permits, and community empowerment initiatives. However, their efforts are confronted by structural challenges, including gender bias, limited resources, and inadequate governmental support. This study highlights how women's leadership in environmental conservation not only overcomes social and institutional barriers but also redefines gender roles in sustainable natural resource governance.Abstrak: Kerusakan hutan di Aceh, termasuk di Kampung Damaran Baru, telah menimbulkan bencana ekologis yang berdampak langsung pada kehidupan masyarakat, khususnya perempuan. Berangkat dari kepedulian terhadap kondisi tersebut, sekelompok perempuan yang dipimpin oleh seorang inisiator membentuk Mpu Uteun, sebuah komunitas perlindungan hutan berbasis perempuan. Penelitian ini bertujuan untuk mengkaji peran dan tantangan yang dihadapi oleh perempuan inisiator dalam upaya pelestarian fungsi hutan melalui kelompok Mpu Uteun. Pendekatan yang digunakan adalah kualitatif dengan metode studi kasus. Teknik pengumpulan data meliputi observasi partisipatif, wawancara mendalam, dan dokumentasi, dengan informan yang dipilih secara purposif. Hasil penelitian menunjukkan bahwa kelompok Mpu Uteun memiliki peran strategis dalam menjaga hutan melalui kegiatan patroli, advokasi perizinan hutan sosial, dan pemberdayaan masyarakat. Namun, keberhasilan mereka tidak lepas dari berbagai tantangan struktural, seperti bias gender, keterbatasan sumber daya, dan minimnya dukungan pemerintah. Temuan ini menunjukkan bahwa kepemimpinan perempuan dalam konservasi hutan tidak hanya mampu mengatasi hambatan sosial, tetapi juga merekonstruksi peran gender dalam tata kelola sumber daya alam yang berkelanjutan.